Para além do soldo: práticas comerciais e formas de ganhos dos governantes das Capitanias do Norte (séc. XVII – XVIII) (Ágora Journal, 2021)
Colonial rulers provided services to the Portuguese Crown to receive an award for their years of service. However, in addition to the mercês to be received in the future, they also sought material gains in the present. The pay received was an attraction factor and many complained about the values, asking for constant increases. Thus, these men sought to supplement their earnings through other practices while governing some captaincy, these practices being sometimes allowed by the Crown, sometimes not. This article intends to analyze the various ways that the rulers of the Northern Captaincies, between the 17th and 18th centuries, found to leverage gains beyond the pay received.